1987
DOI: 10.1177/000456328702400407
|View full text |Cite
|
Sign up to set email alerts
|

The Variability and Dietary Dependence of Urinary Oxalate Excretion in Recurrent Calcium Stone Formers

Abstract: Twenty-two recurrent calcium stone formers had 24-h urinary oxalate excretions on their home diets which were significantly greater than those of 30 normal subjects «()·4X±()·23 rnrnol/d; mean±SD compared with 0·31±0·11; P Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In studying persons who were not selected for having hyperoxaluria, after elimination of colonization with OF there was a low likelihood of demonstrating a change in urinary oxalate, a highly variable measure under even wellcontrolled circumstances. 19 We did not achieve our planned sample size in part because we found a lower prevalence of OF colonization than expected and ended the study. Because our interim analysis showed a strong difference between the groups, we terminated enrollment before reaching our planned sample size.…”
Section: Discussionmentioning
confidence: 92%
“…In studying persons who were not selected for having hyperoxaluria, after elimination of colonization with OF there was a low likelihood of demonstrating a change in urinary oxalate, a highly variable measure under even wellcontrolled circumstances. 19 We did not achieve our planned sample size in part because we found a lower prevalence of OF colonization than expected and ended the study. Because our interim analysis showed a strong difference between the groups, we terminated enrollment before reaching our planned sample size.…”
Section: Discussionmentioning
confidence: 92%
“…This exchange process is proposed to be important for the removal of oxalate from the blood (via the intestine), as well as for maintaining circulating (via the kidneys) and hepatic levels of nutrient sulfate [4, 6, 24, 2931]. Loss of SAT1 in mice led to disturbances in sulfate homeostasis (hyposulfataemia and hypersulfaturia), as well as hyperoxalaemia and hyperoxaluria [24].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these abnormalities or risk factors include: decreased urine volume due to water malabsorption; reduced ionic strength of urine because of electrolyte malabsorption; magnesium and citrate depletion; reduced urine pH; and reduced urinary sulfate and pyrophosphate resulting from protein malabsorption (Bambach et al. 1981;Nordenvall et al, 1983;Smith et al, 1980 intestinal oxalate absorption and urinary oxalate excretion are slightly, but significantly, increased when compared to normal subjects (Brown et al, 1987;Robertson et al, 1978;Tiselius et al, 1981;Zarembski and Hodgkinson, 1969). In addition, Broadus and Thier (1979) found that approximately 50% of the stone-formers exhibited hypercalciuria.…”
Section: Increased Intestinal Absorptionmentioning
confidence: 99%